THE EFFECT OF PRICE DISCOUNT AND HEDONIC SHOPPING VALUE ON IMPULSIVE BUYING AT TIKTOK SHOP - Rasyid, Cynthia Nur; Farida, Lailatul (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The development of technology and information has also led to the existence of social media platforms or electronic commerce to make it easier for people to carry out economic activities in terms of buying and selling goods. The TikTok Shop has become the most widely used social media platform since its emergence as a new feature of the TikTok Application in April 2021. The TikTok Shop attracts consumers with the various conveniences it provides. This study examines the effect of price discounts and hedonic shopping values on impulsive buying. In this study, the type of research that will be conducted by researchers is in the form of quantitative research. The location for conducting this research is in Malang City. The sample of this research is 90 samples. the data used are primary and secondary data with data collection techniques using questionnaires. The variables used are price discount (X1), hedonic shopping value (X2) impulsive buying (Y). The analysis tool used is SmartPLS 3.0. The research results explain that the price discount (X1) has a positive and significant effect on impulsive buying (Y). price discount has a positive and significant effect on impulsive buying. in this study price discounts can attract consumers to make impulsive buying on TikTok Shop Hedonic shopping value (X2) has a positive and significant effect on impulsive buying (Y). there is a sense of pleasure and pleasure when shopping will bring up impulsive buying. The higher the value of hedonism spending, the higher the impulsive buying that occurs